2022
DOI: 10.3390/ani12233273
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Swimming Pool Conditions and Floor Types on White Roman Geese’s Physical Condition Scores and Behaviors in an Indoor Rearing System

Abstract: Biosecurity problems, including the continual risk of avian influenza spread by wild birds, have severely affected traditional free-range waterfowl production systems. Regulations and techniques for indoor goose production require more considerations for animal welfare. This study investigated the effects of swimming pool conditions and different floor types on the physical condition scores and behaviors of indoor-reared White Roman geese. A total of 48 male and 48 female White Roman geese reared from the age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Interpretation: Inability to appropriately perform comfort behaviour is indicated by signs of conjunctivitis, sinusitis, swelling, discharge, occlusion or alteration around the eyes or of the eye structure itself with higher severity of disorders being worse stages -Domestic geese: Williams (2019), Liao et al (2022) Eye disorders have not been reported in quail…”
Section: Abmmentioning
confidence: 99%
See 4 more Smart Citations
“…Interpretation: Inability to appropriately perform comfort behaviour is indicated by signs of conjunctivitis, sinusitis, swelling, discharge, occlusion or alteration around the eyes or of the eye structure itself with higher severity of disorders being worse stages -Domestic geese: Williams (2019), Liao et al (2022) Eye disorders have not been reported in quail…”
Section: Abmmentioning
confidence: 99%
“…Comfort behaviour involves behaviours performed to maintain the feathers and in waterfowl also eyes (e.g. Jones et al., 2009 for Domestic ducks; Liao et al., 2022 for Domestic geese) and nostrils (e.g. O'Driscoll and Broom, 2011 , review by Nicol et al., 2017 for Domestic ducks) clean and in a good condition.…”
Section: Assessmentmentioning
confidence: 99%
See 3 more Smart Citations